Securidaca inappendiculata Polyphenol Rich Extract Counteracts Cognitive Deficits, Neuropathy, Neuroinflammation and Oxidative Stress in Diabetic Encephalopathic Rats via p38 MAPK/Nrf2/HO-1 Pathways - Pang, Xiaojun; Makinde, Emmanuel Ayobami; Eze, Fredrick Nwude; Olatunji, Opeyemi Joshua (Frontiers in Pharmacology, 2021)
Diabetic encephalopathy (DE) is one of the serious emerging complication of diabetes. Securidaca inappendiculata is an important medicinal plant with excellent antioxidant and anti-inflammatory properties. This study investigated the neuroprotective effects of S. inappendiculata polyphenol rich extract (SiPE) against diabetic encephalopathy in rats and elucidated the potential mechanisms of action. Type 2 diabetes mellitus (T2DM) was induced using high fructose solution/intraperitoneal injection of streptozotocin and the diabetic rats were treated with SiPE (50, 100 and 200 mg/kg) for eight weeks. Learning and memory functions were assessed using the Morris water and Y maze tests, depressive behaviour was evaluated using forced swimming and open field tests, while neuropathic pain assessment was assessed using hot plate, tail immersion and formalin tests. After the experiments, acetylcholinesterase (AChE), oxidative stress biomarkers and proinflammatory cytokines, caspase-3 and nuclear factor kappa-light-chain-enhancer of activated B (NF-κB) were determined by ELISA kits. In addition, the expression levels of p38, phospho-p38 (p-p38), nuclear factor erythroid 2–related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) were determined by western blot analyses. The results indicated that SiPE administration significantly lowered blood glucose level, attenuated body weight loss, thermal/chemical hyperalgesia , improved behavioural deficit in the Morris water maze, Y maze test and reduced depressive-like behaviours. Furthermore, SiPE reduced AChE, caspase-3, NF-κB, malonaldehyde (MDA) levels and simultaneously increased antioxidant enzymes activity in the brain tissues of diabetic rats. SiPE administration also significantly suppressed p38 MAPK pathway and upregulated the Nrf2 pathway. The findings suggested that SiPE exerted antidiabetic encephalopathy effects via modulation of oxidative stress and inflammation.